The use of sago waste (Metroxylon sago) and its fermentation product as a feedstuff for growing duck - Antawidjaja, Tata; Bintang, I.A.K; Sinurat, A.P; Kompiang, I.P (Indonesian Animal Sciences Society, 1997)
study were 14 days old local male duckling . The experimental rations were formulated to contain unfermented or fermented of sago waste at graded level of 5, 10, 15 and 20%. A ration without sago waste was also formulated and used as a control diet . All rations were formulated to be isoprotein and isoenergy, i .e . : 17% crude protein and 2,700 kcal ME/kg, respectively. Feed was pelleted and were given ad libitum. The experimental design used was completely randomized with 4 replicates, and each replicate consisted of 10 ducklings . The trial was conducted until 8 weeks old . The fermentation process could increase the nutrient content in sago waste . The unfermented sago waste could be included up to 5% in ration of duckling . At the higher, the final body weight and body weight gain were lowered as compared to the control ration . The fermentation process could be used up to 10%. The use of sago waste did not affect the feed consumption, percentage of carcass and liver weight significantly . Ration with 15% sago waste product a heavier giblets than the control ration . The use of fermented sago waste Â Â at 20% in the ration gave the FCR value higher as compared to control ration . It is necessary to study further the protein quality of fermented sago waste . Â Keywords: Sago waste, fermentation, male duck